2013
DOI: 10.11648/j.ajcem.20130101.14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Juvenile Idiopathic Arthritis: Extended Experience from Bangladesh

Abstract: Objectives: To assess the different clinical aspects of JIA patients as well as the disease activity status during follow-up period. This study also compared its findings with the previous baseline study done in our country. Methodology: A prospective observational study carried out in the department of pediatrics, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh during the study period of January 2004 to December 2012. A total of 415 patients according to ILAR criteria were enrolled in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
3
6
2
Order By: Relevance
“…The mean age of onset of JIA symptoms in our patients was 7.11 ± 3.65 years (range: 8 months–14.5 years), which is not largely different from most studies [9, 14, 25, 27, 28]. However it is higher than the mean age in a large study which included 3167 patients from Europe and Latin America where mean age of onset of JIA symptoms was 5.8 years [21] but lower than a mean age of 9.5 years recorded in a cohort from Taiwan of 195 patients [22].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The mean age of onset of JIA symptoms in our patients was 7.11 ± 3.65 years (range: 8 months–14.5 years), which is not largely different from most studies [9, 14, 25, 27, 28]. However it is higher than the mean age in a large study which included 3167 patients from Europe and Latin America where mean age of onset of JIA symptoms was 5.8 years [21] but lower than a mean age of 9.5 years recorded in a cohort from Taiwan of 195 patients [22].…”
Section: Discussioncontrasting
confidence: 75%
“…Few studies showed an overall equal or higher male-to-female ratio [4, 6, 15, 25, 26]; this higher male percentage was possibly related to a higher ERA in one series [3, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…In this prospective observational study, there was male predominance. Similar results with male predominance was found in few other studies done in our country 18‐20 . The reason for male predominance in our country could be due to male preferences in all aspects in family and society.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results with male predominance was found in few other studies done in our country. [18][19][20] The reason for male predominance in our country could be due to male preferences in all aspects in family and society. Another reason for higher male frequency could be due to higher percentage of ERA (37%) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective observational study carried out in the same set up also found more males than females (M:F ratio approximately 2:1), and most of the patients were in the age group of 11-15 years. 13 This different result regarding sex distribution and types of JIA found in this study could be due to social or geographical difference. In the present study, maximum number of patients were suffering from ERA (32.0%), followed by SJIA, polyarticular and oligo articular JIA (figure 1).…”
Section: Discussioncontrasting
confidence: 53%